2015
DOI: 10.4102/aej.v3i1.139
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on an impact evaluation of the Grade R programme: Method, results and policy responses

Abstract: This paper describes the expansion since 2001 of a public pre-school programme in South Africa known as ‘Grade R’, summarises the findings from an impact evaluation of the introduction of Grade R, discusses the policy recommendations flowing from the evaluation and reflects on the process of implementing the recommendations. The Grade R programme has expanded dramatically, to the point where participation is nearly universal. Although a substantial literature points to large potential benefits from pre-school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As far as could be established, similar findings have not previously been reported. Samuels et al (2015) did an impact evaluation of a Grade R programme. Mashalaba et al (2015) did an implementation evaluation of the business process services (BPS) incentive programme undertaken by the Department of Trade and Industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as could be established, similar findings have not previously been reported. Samuels et al (2015) did an impact evaluation of a Grade R programme. Mashalaba et al (2015) did an implementation evaluation of the business process services (BPS) incentive programme undertaken by the Department of Trade and Industry.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of outcome, under the ambit of an impact assessment, could entail a knowledge increase, and a behavioural and/or an attitudinal change (Babbie & Mouton, 2011). Because of the fact that this study controlled for the influence of previous training, the view of Samuels et al (2015), who found that an educational intervention had limited impact on later educational outcomes, is pertinent.…”
Section: Inputsmentioning
confidence: 99%
“…The upper-middle-income countries (defined as having per capita incomes from $4,126 to $12,735) include Colombia ($6,990), Macedonia ($4,870), and the Chinese province of Yunnan ($4,435). These countries represent several world regions: Eastern Europe and Central Asia (Armenia, Georgia, Macedonia, and Ukraine), Latin America (Bolivia and Colombia), Sub-Saharan 3 As Samuels et al (2015) acknowledges, the Grade R evaluation was not a randomized control trial. Since the program was already in place, researchers matched participant and nonparticipant students with similar characteristics.…”
Section: Datamentioning
confidence: 99%
“…Evaluations and research have pointed to the generally poor mathematics early learning experiences of South African learners (Feza 2013). In addition, studies have revealed that Grade R (the reception year) is subjected to disturbing, multifaceted challenges that are a cause for concern among stakeholders, who view current practices as being out of step with policy guidelines (Artmore, Van Niekerk & Ashley-Cooper 2012;Excell & Linington 2011;Hoadley 2013;Samuels et al 2015). Among the challenges facing this sector are poorly trained educators who have a minimum of content knowledge of mathematics (Spaull 2013), have poor classroom practices (Feza 2013) and are inept at the use of technology (Mdlongwa 2012).…”
Section: Introductionmentioning
confidence: 99%